Optimizing Broiler Chicken Distribution Using the North West Corner, Least Cost, and Vogel's Approximation Methods - Ahmad Saiful Ma’ruf; Kajinada Ilham; Lyra Noor Edy Thania (Takaza Innovatix Labs Ltd., 2026)
This study applies a transportation algorithm to minimize distribution costs for MSMEs as Broiler Chicken Suppliers through a case study of product distribution to several customer locations. The data used include the supply capacity of three warehouses, customer demand, and shipping costs per kilogram calculated based on the operational costs of pick-up vehicles. This study aims to compare the efficiency of the Northwest Corner (NWC), Least Cost (LC), and Vogel's Approximation Method (VAM) methods in determining distribution allocation with minimum costs. The calculation results show that the Northwest Corner method produces a total distribution cost of Rp114,180, while the Least Cost and Vogel's Approximation Method produce a lower distribution cost of Rp110,300. Thus, the LC and VAM methods are more efficient than the NWC method in solving the transportation problem in this case study. Based on the analysis results, the Vogel's Approximation Method (VAM) was chosen as the best solution because in addition to producing minimum distribution costs, this method also considers the penalty value so that the initial solution obtained is closer to the optimal condition. This research is expected to be a reference for MSMEs in determining more effective and efficient distribution strategies